SUICIDE AND THE TRANSEXUAL AND TRANSVESTITE POPULATION: WHAT MAKES THESE PEOPLE NOT WANT TO LIVE ANYMORE? - Miranda, Gabriel; dos Anjos, Rafael; Silva, Ricardo; Lizak Zolfan, Shirlei (Health and Society, 2024)
Suicide is a complex phenomenon affecting over 800,000 people annually, according to WHO data (2019). The transgender and travesti community, despite advancements in the struggle for rights and recognition, continues to suffer intensely from stigma and discrimination, as pointed out by ABGLT (2014). Authors such as Brosin and Tokarski (2017) highlight that the persistence of prejudice is deeply rooted in the normalization of heterosexuality, which exerts constant pressure on individuals who diverge from this standard. For the transgender and travesti population, the process of name and gender rectification can be particularly challenging, as noted by Ribeiro (2001). This moment is often marked by stress, violence, and the possibility of rejection—factors that can lead to serious psychological problems, including suicide. However, there is a significant gap in the academic literature regarding the interrelation between suicide and the transgender and travesti population, especially in the context of São Paulo. Given this absence of in-depth studies, there is a need to investigate the psychosocial factors that directly impact the mental health of this population, understand the reasons that lead them to consider suicide, and highlight the fundamental role of psychologists and public health systems in this context.